Heart of Buddha, heart of China: the life of Tanxu, a twentieth-century monk - Carter, James Hugh (Oxford University Press, 2011)
Prologue : The present past -- Not far from anywhere -- Leaving home -- New worlds -- Family -- Conditioned arising -- Ice and fire -- Famine and flight -- Qingdao -- Life during wartime -- Forward to the past -- Epilogue : the past in the present